Studies in modern India political thought: the moderates and the extremists - Goyal, O.P. (Allahabad, 1964)
The book is an attempt to delineate the political thought of the Moderate and Extremist leaders of the 19th century and the early 20th century. It is a result of my researches and is based on my teaching experience of Modern Indian Political Thought to the Post Graduate students of Panjab University, Chandigarh. The book opens with a background chapter which discusses the development of nationalism in India, Nature of Modern Indian Political Thought and Western influences thereupon. Polit Thought and Political theory have been carefully distinguished and the need for the study of Political Thought is emphasized. The second chapter on Raja Ram Mohan Roy owes its inspiration to a lecture by Justice Gajendra Gadkar, Supreme Court of India. In the third Chapter on the Political Thought of Dadabhai Naoroji, his theory of the Drain has been discussed extensively and a comparison has been drawn with Lenin's theory of Imperialism. The fourth chapter is on the Political Thought of Justice M.G. Ranade.
Keywords: Political Science